Proceedings of the 21st International Conference on Enterprise Information Systems 2019
DOI: 10.5220/0007675900950106
|View full text |Cite
|
Sign up to set email alerts
|

Automated Measurement of Technical Debt: A Systematic Literature Review

Abstract: Background: Technical Debt (TD) is a quite complex concept that includes several aspect of software development. Often, people talk about TD as the amount of postponed work but this is just a basic approximation of the concept that includes many aspects that are technical and managerial. If TD is managed properly, it can provide a huge advantage but it can also make projects unmaintainable, if not. Therefore, being able of measuring TD is a very important aspect for a proper management of the development proce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…The first scientific workshop titled "Workshop on Managing Technical Debt" ( [14]) was organized already in 2010. Khomyakov et al [36] found 603 papers published between 2011 and 2017 related to the automated measurement of technical debt. According to Lenarduzzi et al [38] in 2018 alone (between March 2018 to December 2018) 384 unique papers were published related to technical debt research.…”
Section: Related Workmentioning
confidence: 99%
“…The first scientific workshop titled "Workshop on Managing Technical Debt" ( [14]) was organized already in 2010. Khomyakov et al [36] found 603 papers published between 2011 and 2017 related to the automated measurement of technical debt. According to Lenarduzzi et al [38] in 2018 alone (between March 2018 to December 2018) 384 unique papers were published related to technical debt research.…”
Section: Related Workmentioning
confidence: 99%
“…Recently, Khomyakov et al [19] investigated existing tools for the measurement and analysis of TD, focusing on quantitative methods that could also be automated. They selected 21 papers out of 331 retrieved.…”
Section: Previous Slr Smentioning
confidence: 99%
“…Year Goal [11] 2012 Understanding the nature of TD [5] 2015 TD management and TD classification [14] 2015 Financial approaches for managing TD [15] 2016 TD payment prioritization [16] 2016 TD management strategies, TD taxonomy [17] 2017 TD management elements [18] 2017 TD in Agile development [12] 2018 Managing architectural TD [13] 2018 TD types, management strategies [19] 2019 TD tools…”
Section: Idmentioning
confidence: 99%
“…In light of the existing literature, it is evident that during the last 10 years, TD has been heavily investigated to understand its functioning from various perspectives. For example, TD effort, [ 6 ] tools, [ 20 ] and types, management strategies [ 21 ] and managing architectural TD [ 22 ] as well as TD in terms of agile development, [ 23 ] management elements, [ 24 ] and prioritization, [ 5 ] etc. Meanwhile, NTD has remained latent and relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%